The Contribution of Artificial Intelligence Technologies in Refining the Arabic Language Skills of Its Native Speakers: Achieved and Possible - Alsaied, Mohamad Abdullah (Journal of Ecohumanism, 2024)
This study aims to shed light on the applications of Artificial Intelligence (AI) in improving Arabic language skills for speakers. It involves digitizing the language, developing computer programming, and adapting it to Arabic language learners to enhance the learning and teaching process. This study emphasizes the significance of implementing this project, as it can open up new horizons in educational curricula and teaching techniques. Moreover, it can contribute to spreading the use of the Arabic language and facilitating its acquisition, exchange, and dissemination globally, leading to positive outcomes on all levels. The current study also presents the most crucial benefits resulting from the digitization of the Arabic language, including supporting the self-learning strategy that has dominated most traditional methods. It also reinforces the status of the Arabic language in cognitive and scientific systems, blogs, and speech communication. One of the benefits is the easy acquisition and exchange of Arabic language skills, especially with the availability of various smartphone applications that have become indispensable in this era. Furthermore, the study addresses the significant challenges and difficulties facing this project and suggests appropriate solutions to overcome them. To what extent has the Arabic language benefited from this new digital transformation based on AI in the present era? And to what extent can the Arabic language rely on AI in the future so that its speakers can enhance their linguistic skills and proficiency in writing and speaking?